Description of two new species of Leptinopterus Hope (Coleoptera: Lucanidae: Lucaninae) with notes on the taxonomy and natural history of the genus - Grossi, Paschoal Coelho (Zootaxa, 2009)
Two new species of Leptinopterus are described, both from southern Brazil: L. asketus new species and L. assimilis new species. Two new synonymies are also made; L. rotundicollis Lüderwaldt and L. luederwaldti de Moraes are synonymyzed with L. tibialis (Eschscholtz). The correct identities of two unavailable names are discussed: “L. nitidus ab. lepidus” with L. affinis Parry and “L. elegans ab. catharinensis” with L. gracilis Boileau. For the first time, some natural history notes for five species of Leptinopterus are reported and some information on their behavior is also given. The identity of Leptinopterus gracilis is correctly determined after an examination of a picture of the holotype.